A neodymium iron boron magnet and a method for preparing the same
Through modified NdFeB magnetic powder and high-temperature sintering technology, the problem of high cost of rare earth elements in NdFeB magnet production is solved, cost reduction and magnetic performance are achieved, and the processing performance and corrosion resistance of magnets are improved.
Patent Information
- Application Number
- CN202111171168.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-08
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-10-08
AI Technical Summary
The high cost and magnetic performance impact of rare earth elements in the production of neodymium iron boron magnets, and the existing alternative methods for rare earth elements have limitations on cost reduction but performance losses.
Modified NdFeB magnetic powder is used to form an organic cladding layer by polymerizing the surface of NdFeB magnetic powder, and the distribution of erbium elements is optimized during high-temperature sintering, combining appropriate amounts of gadolinium, yttrium and other The ratio of elements reduces production costs and maintains magnetic performance.
Reduce production costs without reducing magnetic properties, improve the processing performance and corrosion resistance of magnets, improve the distribution of erbium elements through high-temperature sintering, and form a uniform magnet.
Smart Images

Figure BDA0003293230230000021 
Figure BDA0003293230230000022 
Figure BDA0003293230230000051
Abstract
Description
Technical Field
[0001] The present application belongs to the field of magnet technology, and specifically relates to a neodymium iron boron magnet and a preparation method thereof. Background Art
[0002] NdFeB magnets are tetragonal crystals formed by neodymium, iron and boron. They are permanent magnets with magnetic properties second only to absolute zero holmium magnets and are also the most commonly used rare earth magnets. NdFeB magnets are widely used in electronic products such as hard disks, mobile phones, headphones and battery-powered tools.
[0003] In the production process of NdFeB magnets, rare earth elements such as terbium and dysprosium are usually added to improve the magnetism of the magnets, resulting in high production costs for NdFeB magnets, which limits the choice of NdFeB magnets by many downstream manufacturers. The commonly used method is to use relatively low-priced cerium to replace these expensive rare earth elements, thereby reducing production costs. However, excessive addition of cerium will seriously affect the performance of the magnets. Therefore, there are certain limitations to the use of cerium to replace rare earth elements.
[0004] For the above reasons, it is necessary to develop a new NdFeB magnet that does not affect the magnetic properties of the magnet while reducing the addition of expensive rare earth elements and reducing costs. Summary of the invention
[0005] In order to solve the problem of high production cost caused by adding more rare earth elements in NdFeB magnets, the present application discloses a NdFeB magnet and a preparation method thereof.
[0006] In a first aspect, the present application provides a neodymium iron boron magnet, which adopts the following technical solution:
[0007] A neodymium iron boron magnet is obtained by high-temperature sintering of neodymium iron boron magnetic powder. The neodymium iron boron magnetic powder comprises the following components in percentage by mass: 1-3% erbium, 0.5-2% yttrium, 2-4% gadolinium, 20-30% praseodymium and neodymium, 0.5-2% boron, 0.1-1% aluminum, 0.05-0.5% zirconium, 0.05-0.3% copper, 0.1-1% cobalt, and the remainder is pure iron.
[0008] Preferably, the NdFeB magnetic powder is modified NdFeB magnetic powder, and the modification method is:
[0009] (1) adding unmodified NdFeB magnetic powder to a modifier solution and stirring for 10-30 minutes to obtain a NdFeB magnetic powder solution with a surface grafted modifier;
[0010] (2) adding an unsaturated monomer and an initiator to the solution obtained in step (1), stirring and dispersing the unsaturated monomer evenly, so that the unsaturated monomer is evenly adsorbed on the surface of the NdFeB magnetic powder, and then performing a polymerization reaction under polymerization conditions to polymerize the unsaturated monomers and coat the surface of the NdFeB magnetic powder to obtain modified NdFeB magnetic powder.
[0011] Preferably, the structural formula of the above-mentioned modifier is:
[0012]
[0013] The preparation method of the modifier is as follows: 4-amino-1,6-heptadiene and a Pt-PMVS catalyst are added into a reaction kettle, the temperature is raised to 90° C., triethoxysilane is gradually added dropwise under stirring for 3-4 hours, the addition is completed, and then the reaction is continued for 3-4 hours, and the catalyst is removed by filter pressing to obtain a modifier, wherein the molar ratio of 4-amino-1,6-heptadiene to triethoxysilane is 1:1, the addition amount of the Pt-PMVS catalyst is 30-50 ppm, and the reaction equation is:
[0014]
[0015] Preferably, in the above step (1), the mass percentage of the modifier to the unmodified NdFeB magnetic powder is 0.5-2%.
[0016] Preferably, the modifier solution in the above step (1) is an ethanol solution of the modifier.
[0017] Preferably, the unsaturated monomer added in the above step (2) accounts for 1-5% by mass of the unmodified NdFeB magnetic powder; the unsaturated monomer in the step (2) is an aliphatic unsaturated monomer; and the initiator in the step (2) is azobisisobutyronitrile or benzoyl peroxide.
[0018] Preferably, the step (2) is carried out under nitrogen protection, and the polymerization conditions in the step (2) are: heating to 80-85° C. and stirring the reaction for 1-2 hours.
[0019] In a second aspect, the present application provides a method for preparing a neodymium iron boron magnet, using the following technical solution:
[0020] A method for preparing a neodymium iron boron magnet comprises the following steps:
[0021] (A) melting, hydrogen crushing, jet milling and modifying the raw materials according to the proportion to obtain modified NdFeB magnetic powder;
[0022] (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a NdFeB magnet blank;
[0023] (C) Sintering the NdFeB magnet blank at high temperature under vacuum to obtain a NdFeB magnet.
[0024] Preferably, the above step (C) is specifically as follows: heating the NdFeB magnet blank to 300-400°C under vacuum for degreasing for 1-3 hours, then heating to 500-800°C for 1-2 hours, and finally heating for high temperature sintering to obtain the NdFeB magnet.
[0025] Preferably, the high temperature sintering is performed at a temperature of 1050-1100° C. and for a time of 4-6 hours.
[0026] This application has the following beneficial effects:
[0027] (1) The NdFeB magnet of the present application adds 1-3% erbium to replace praseodymium and neodymium in the magnetic powder formula, which reduces the production cost without reducing the magnetic properties. Moreover, the use of 2-4% gadolinium is also conducive to reducing the production cost without affecting the magnetic properties of the NdFeB magnet. In addition, the addition of 0.5-2% yttrium can improve the processing performance and make it easier to process.
[0028] (2) The NdFeB magnetic powder used in this application is a modified NdFeB magnetic powder. The modifier is first grafted onto the surface of the NdFeB magnetic powder, and then a firm organic coating layer is formed on the surface of the magnetic powder through the polymerization of unsaturated monomers, which plays an effective isolation role and prevents the magnetic powder from being oxidized during storage, thereby affecting the performance of the magnetic powder and then the performance of the magnet;
[0029] (3) The high temperature sintering temperature in the present application is relatively high, 1050-1100°C, which can improve the uniform distribution of erbium elements in the guard and increase the coercive force. DETAILED DESCRIPTION
[0030] The present application will now be further described in detail with reference to embodiments.
[0031] Example 1
[0032] The mass percentage of each component is: erbium 1%, yttrium 2%, gadolinium 3%, praseodymium and neodymium 23%, boron 2%, aluminum 0.2%, zirconium 0.3%, copper 0.1%, cobalt 0.4%, and pure iron as the balance.
[0033] (A) melting, hydrogen crushing and jet milling the raw materials according to the ratio to obtain unmodified NdFeB magnetic powder; then, under nitrogen protection, 0.5g of the modifier is uniformly dispersed in an appropriate amount of ethanol, 100g of the unmodified NdFeB magnetic powder is added, and the mixture is stirred at a speed of 400r / min for 10 minutes, and then 3g of methyl methacrylate and 0.01g of AIBN are added under stirring, and stirring is continued for 10 minutes, and the temperature is raised to 80°C and stirred for reaction for 2 hours to complete the polymerization reaction, and the mixture is filtered, washed with ethanol and dried to obtain modified NdFeB magnetic powder;
[0034] (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a rough NdFeB magnet;
[0035] (C) The NdFeB magnet blank is heated to 300°C under vacuum for degreasing for 3 hours, then heated to 500°C for 2 hours to remove the gas adsorbed on the surface of the magnetic powder, and finally heated to 1050-1100°C for high-temperature sintering for 4 hours to obtain the NdFeB magnet.
[0036] Example 2
[0037] The mass percentage of each component is: erbium 3%, yttrium 0.5%, gadolinium 3.5%, praseodymium and neodymium 28%, boron 0.6%, aluminum 0.8%, zirconium 0.1%, copper 0.3%, cobalt 0.8%, and the balance is pure iron.
[0038] (A) Melting, hydrogen crushing and jet milling the raw materials according to the ratio to obtain unmodified NdFeB magnetic powder; then, under nitrogen protection, 1g of the modifier is uniformly dispersed in an appropriate amount of ethanol, 100g of the unmodified NdFeB magnetic powder is added, and the mixture is stirred at a speed of 400r / min for 20 minutes, and then 1g of methyl methacrylate and 0.01g of AIBN are added under stirring, and stirring is continued for 10 minutes. The temperature is raised to 85°C and stirred for reaction for 1 hour to complete the polymerization reaction, and the mixture is filtered, washed with ethanol and dried to obtain modified NdFeB magnetic powder;
[0039] (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a rough NdFeB magnet;
[0040] (C) The NdFeB magnet blank is heated to 350°C under vacuum for degreasing for 2 hours, then heated to 600°C for 1 hour to remove the gas adsorbed on the surface of the magnetic powder, and finally heated to 1050-1100°C for high-temperature sintering for 5 hours to obtain a NdFeB magnet.
[0041] Example 3
[0042] The mass percentage of each component is: erbium 1.8%, yttrium 0.8%, gadolinium 1.5%, praseodymium and neodymium 24%, boron 1.5%, aluminum 0.4%, zirconium 0.5%, copper 0.2%, cobalt 0.3%, and pure iron as the balance.
[0043] (A) Melting, hydrogen crushing and jet milling the raw materials according to the ratio to obtain unmodified NdFeB magnetic powder; then, under nitrogen protection, 2g of the modifier is uniformly dispersed in an appropriate amount of ethanol, 100g of the unmodified NdFeB magnetic powder is added, and the mixture is stirred at a speed of 400r / min for 30 minutes, and then 5g of methyl methacrylate and 0.01g of BPO are added under stirring, and stirring is continued for 10 minutes. The temperature is raised to 85°C and stirred for reaction for 1 hour to complete the polymerization reaction, and the mixture is filtered, washed with ethanol and dried to obtain modified NdFeB magnetic powder;
[0044] (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a NdFeB magnet blank;
[0045] (C) The NdFeB magnet blank is heated to 400°C under vacuum for degreasing for 1 hour, then heated to 700°C for 1 hour to remove the gas adsorbed on the surface of the magnetic powder, and finally heated to 1050-1100°C for high-temperature sintering for 6 hours to obtain the NdFeB magnet.
[0046] Example 4
[0047] The mass percentage of each component is: erbium 2%, yttrium 1%, gadolinium 3%, praseodymium and neodymium 25%, boron 0.92%, aluminum 0.5%, zirconium 0.2%, copper 0.15%, cobalt 0.5%, and the balance is pure iron.
[0048] (A) Melting, hydrogen crushing and jet milling the raw materials according to the ratio to obtain unmodified NdFeB magnetic powder; then, under nitrogen protection, 1.5 g of the modifier is uniformly dispersed in an appropriate amount of ethanol, 100 g of the unmodified NdFeB magnetic powder is added, and the mixture is stirred at a speed of 400 r / min for 20 minutes, and then 2 g of methyl methacrylate and 0.01 g of AIBN are added under stirring, and stirring is continued for 10 minutes. The temperature is raised to 85° C. and stirred for 1 hour to complete the polymerization reaction, and the mixture is filtered, washed with ethanol and dried to obtain modified NdFeB magnetic powder 4;
[0049] (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a NdFeB magnet blank;
[0050] (C) The NdFeB magnet blank is heated to 350°C under vacuum for degreasing for 2 hours, then heated to 600°C for 1 hour to remove the gas adsorbed on the surface of the magnetic powder, and finally heated to 1050-1100°C for high-temperature sintering for 4 hours to obtain the NdFeB magnet.
[0051] Comparative Example 1
[0052] The mass percentage of each component is: erbium 2%, yttrium 1%, gadolinium 3%, praseodymium and neodymium 25%, boron 0.92%, aluminum 0.5%, zirconium 0.2%, copper 0.15%, cobalt 0.5%, and the balance is pure iron.
[0053] (A) Melting, hydrogen crushing and jet milling the raw materials according to the ratio to obtain unmodified NdFeB magnetic powder; then, under nitrogen protection, 1.5g of silane coupling agent KH570 was uniformly dispersed in an appropriate amount of ethanol, 100g of unmodified NdFeB magnetic powder was added, and stirred at a speed of 400r / min for 20 minutes, and then 2g of methyl methacrylate and 0.01g of AIBN were added under stirring, and stirring was continued for 10 minutes. The temperature was raised to 85°C and stirred for 1 hour to complete the polymerization reaction, and the modified NdFeB magnetic powder 4 was obtained by suction filtration, ethanol washing and drying;
[0054] (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a NdFeB magnet blank;
[0055] (C) The NdFeB magnet blank is heated to 350°C under vacuum for degreasing for 2 hours, then heated to 600°C for 1 hour to remove the gas adsorbed on the surface of the magnetic powder, and finally heated to 1050-1100°C for high-temperature sintering for 4 hours to obtain the NdFeB magnet.
[0056] Comparative Example 2
[0057] The mass percentage of each component is: erbium 2%, yttrium 1%, gadolinium 3%, praseodymium and neodymium 25%, boron 0.92%, aluminum 0.5%, zirconium 0.2%, copper 0.15%, cobalt 0.5%, and the balance is pure iron.
[0058] (A) Melting, hydrogen crushing and jet milling the raw materials according to the ratio to obtain unmodified NdFeB magnetic powder; then, under nitrogen protection, 1.5g of silane coupling agent KH550 was uniformly dispersed in an appropriate amount of ethanol, 100g of unmodified NdFeB magnetic powder was added, and the mixture was stirred at a speed of 400r / min for 20 minutes, and then 2g of methyl methacrylate and 0.01g of AIBN were added under stirring, and stirring was continued for 10 minutes. The temperature was raised to 85°C and stirred for 1 hour to complete the polymerization reaction, and the mixture was filtered, washed with ethanol and dried to obtain modified NdFeB magnetic powder 4;
[0059] (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a NdFeB magnet blank;
[0060] (C) The NdFeB magnet blank is heated to 350°C under vacuum for degreasing for 2 hours, then heated to 600°C for 1 hour to remove the gas adsorbed on the surface of the magnetic powder, and finally heated to 1050-1100°C for high-temperature sintering for 4 hours to obtain the NdFeB magnet.
[0061] The magnetic properties of the NdFeB magnets prepared in the above Examples 1-4 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1.
[0062] Table 1
[0063]
[0064] The magnet accelerated corrosion test adopts the PCT method (temperature is 120° C., relative humidity is 100% saturation mode, and absolute vapor pressure is 0.2 MPa).
[0065] As can be seen from Table 1, the weight loss rate of the NdFeB magnets prepared in Examples 1-4 after 10 days of PCT test is 0.011-0.023 mg / cm 2, all have good corrosion resistance, which may be due to the presence of amino groups in the modifiers used in Examples 1-4. The ammonia generated during the degreasing process can react with aluminum with a greater affinity for nitrogen to form aluminum nitride, which can effectively improve the chemical stability of the grain boundary phase, refine the grains, improve the distribution of the grain boundary phase, and increase the density of the magnet, thereby improving the corrosion resistance and magnetic properties of the magnet. Compared with Example 4, the modifier used in the modified NdFeB magnetic powder in Comparative Example 1 is the silane coupling agent KH570, and the weight loss rate after 10 days of PCT test is 0.045mg / cm 2 The reason may be that there is no amino group in KH570, so aluminum nitride that can improve the corrosion resistance cannot be formed, resulting in the decrease of the corrosion resistance of Comparative Example 1. Comparative Example 2 Compared with Example 4, the modifier used for modifying the NdFeB magnetic powder is the silane coupling agent KH550. The weight loss rate after 10 days of PCT test is 0.218 mg / cm 2 Although there are amino groups in KH550, the unsaturated monomer cannot form a good coating effect on the magnetic powder due to the absence of double bonds. During the orientation pressing process of the magnetic powder in the magnetic field, the magnetic powder is exposed to a small amount of oxygen, resulting in a decrease in the magnetic properties of the magnet prepared in Comparative Example 2.
[0066] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A neodymium iron boron magnet, characterized in that: The NdFeB magnetic powder is obtained by high temperature sintering. The NdFeB magnetic powder includes the following components in percentage by mass: 1-3% erbium, 0.5-2% yttrium, 2-4% gadolinium, 20-30% praseodymium-neodymium, 0.5-2% boron, 0.1-1% aluminum, 0.05-0.5% zirconium, 0.05-0.3% copper, 0.1-1% cobalt, and the remainder is pure iron; The NdFeB magnetic powder is modified NdFeB magnetic powder, and the modification method is as follows: (1) adding unmodified NdFeB magnetic powder to a modifier solution and stirring for 10-30 minutes to obtain a NdFeB magnetic powder solution with a surface grafted modifier; (2) adding an unsaturated monomer and an initiator to the solution obtained in step (1), stirring and dispersing the unsaturated monomer uniformly, so that the unsaturated monomer is uniformly adsorbed on the surface of the NdFeB magnetic powder, and then performing a polymerization reaction under polymerization conditions to polymerize the unsaturated monomers and coat the surface of the NdFeB magnetic powder to obtain modified NdFeB magnetic powder; The structural formula of the modifier is: The unsaturated monomer added in step (2) accounts for 1-5% by mass of the unmodified NdFeB magnetic powder; the unsaturated monomer in step (2) is an aliphatic unsaturated monomer; the initiator in step (2) is azobisisobutyronitrile or benzoyl peroxide; The high temperature sintering temperature is 1050-1100° C. and the time is 4-6 hours.
2. The NdFeB magnet according to claim 1, wherein: In the step (1), the mass percentage of the modifier to the unmodified NdFeB magnetic powder is 0.5-2%.
3. The NdFeB magnet according to claim 1, wherein: The modifier solution in step (1) is an ethanol solution of the modifier.
4. The NdFeB magnet according to claim 1, wherein: The step (2) is carried out under nitrogen protection. The polymerization conditions in the step (2) are: heating to 80-85° C. and stirring the reaction for 1-2 hours.
5. A method for preparing a NdFeB magnet as claimed in any one of claims 1 to 4, characterized in that: The steps include: (A) melting, hydrogen crushing, jet milling and modifying the raw materials according to the proportion to obtain modified NdFeB magnetic powder; (B) orienting and pressing the modified NdFeB magnetic powder in a magnetic field to obtain a NdFeB magnet blank; (C) Sintering the NdFeB magnet blank at high temperature under vacuum to obtain a NdFeB magnet.
6. The method for preparing a NdFeB magnet according to claim 5, wherein: The step (C) is specifically as follows: heating the NdFeB magnet blank to 300-400°C under vacuum for degreasing for 1-3 hours, then heating to 500-800°C for keeping for 1-2 hours, and finally heating for high temperature sintering to obtain the NdFeB magnet.
Citation Information
Patent Citations
Preparing method of modified neodymium-iron-boron magnetic powder, modified neodymium-iron-boron magnetic powder and neodymium-iron-boron sintering body
CN108231310A
R-T-B system rare earth permanent magnet
CN1540686A